Direct synthesis of β-ketophosphonates and vinyl phosphonates from alkenes or alkynes catalyzed by CuNPs/ZnO1. Issue 81 (3rd September 2015) - Gutierrez, Victoria; Mascaró, Evangelina; Alonso, Francisco; Moglie, Yanina; Radivoy, Gabriel
<x xml:space="preserve">Abstract</x> Ligand- and base-free direct synthesis of β-keto- and vinyl phosphonates catalysed by CuNPs/ZnO under air. Selectivity dependent on alkyne nature.